Snoring and Obstructive Sleep Apnea Syndrome: A reflection on the role of Dentistry in the current scientific scenario - e Rangel, Ângela Jeunon de Alencar (2012)
Introduction: Finally the dentist has awaken to the fact that by being a health professional, he has as primary function to take good care of the welfare of patients. In face of this challenge, the dentist starts to understand his role in the treatment of snoring and of obstructive sleep apnea and hypopnea. Objective: The current paper has the purpose of discussing the role of this professional in the diagnosis and treatment of these diseases, most specifically of the therapy involving inter-occlusal devices, emphasizing the importance of multidisciplinarity in the reestablishment of the quality of life of the patient. © 2012 Dental Press Journal of Orthodontics.